Modifikasi Instalasi Biogas Kotoran Sapi Tipe Fixed Dome di Anggota Kelompok Tani Kanti Sembada Desa Candikuning - Roi Zulkarnaen (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The purpose of this study were to design fixed-dome type bioreactor and to measure its performance. through biogas prosessing that was made from cow dung feces with optimal process temperature. The components of the bioreactor were: biomass inlet, digestion tank, the bioreactor mantle, the bioreactor dome, and outlet basin for sludge. Through design analysing were obtain spesification of bioreactor was 426 cm long, diameter of 160 cm, 200 cm height and a total volume of 3.04 m3. The mantle of bioreactor which 10 cm thick was filled with sand. Results of bioreactor performance test showed that for 35 days the temperature of the biomass in the bioreactor was greater than the ambient temperature. The larger gap between both temperature was 6.8° C which achieved at day 27th of fermentation and the biomass temperature was 31° C. The gas pressure inside the bioreactor increased in accordance with the increase of biomass temperature. Biogas production per day achieved at average of 2.,31 liter with 2.5 cmH2O preassure.